Oral Health Knowledge, Attitudes, and Behaviors Among University Students in Jeddah, Saudi Arabia - Farsi NJ; Merdad Y; Mirdad M; Batweel O; Badri R; Alrefai H; Alshahrani S; Tayeb R; Farsi J (Dove Medical Press, 2020)
Nada J Farsi,1 Yasser Merdad,2 Mohammed Mirdad,3 Omar Batweel,4 Rawan Badri,5 Hind Alrefai,6 Sultanah Alshahrani,7 Rawan Tayeb,8 Jamila Farsi9 1Department of Dental Public Health, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 2Department of Restorative and Aesthetic Dentistry, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 3Ministry of Health, Jeddah, Saudi Arabia; 4Ministry of Health, Makkah, Saudi Arabia; 5Department of Periodontics, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 6Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 7Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 8Ministry of Health, Riyadh, Saudi Arabia; 9Department of Oral Biology, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Nada J FarsiDepartment of Dental Public Health, Faculty of Dentistry, King Abdulaziz University, P.O. Box 80200, Jeddah 21589, Saudi ArabiaTel +966126400000Fax +966126952437Email njfarsi@kau.edu.saPurpose: This study aimed to evaluate oral health knowledge, attitudes, and behaviors among a sample of senior students at King Abdulaziz University (KAU), and to assess differences among these factors between genders.Methods: A total of 1177 senior university students at KAU were included in this cross-sectional study. Participants were selected by stratified random sampling. KAU has three main streams categorized by field of study. One faculty was randomly selected from each stream. Information regarding oral health knowledge, attitudes, and behaviors was collected with a validated self-administered questionnaire. A knowledge score was calculated, and predictors of oral health knowledge were assessed by linear regression.Results: In general, the mean oral health knowledge score of females (8.1 ± 1.8) was significantly higher than that of males (7.2 ± 2.1) out of 13. Relative to males, females reported a greater frequency of teeth cleaning and of using a toothbrush with proper technique (p < 0.001). Females were also more likely to have ever visited a dentist than males (95% and 86%, respectively). The linear regression model revealed that students in non-medical faculties and those who were not shown how to brush their teeth by a dentist had lower oral health knowledge scores, than their counterparts. Students older than 22 years and females were more likely to have higher oral health knowledge scores than were their counterparts.Conclusion: Oral health knowledge was relatively low among the university students, but females showed better oral health knowledge and behaviors than males did.Keywords: oral health, attitudes, behaviors, university students